Klasifikasi dan Manfaat RAID (Redundant Array of Inexpensive Disks) - Basuki Winoto; Agus Fatulloh (JURNAL INTEGRASI, 2012)
RAID was intended to resolve the need of having an abundant storage capacity by aggregating multiple disks. The ability to mirror one disk to another allows user obtaining a very basic fault tolerant system with RAID. Mirror disk provides an exact copy of the mirrored one. In the event of one disk failed, the data contained in it can be rebuilt based on the copy stored in the mirror disk. The use of Hamming-code parity provides fault tolerant system similar to mirroring with more usable capacity in aggregate. Parity requires less space per chunk of data, yet it has the ability to reconstruct the missing data. Parity data can be stored in a single disk or can be distributed to multiple disks for a better write performance. An improvement in fault tolerant level can be achieved by storing the parity data twice as much that will allow the system to rebuild the data in the event of two disks failure at the same time. This paper covers the classification of basic and hybrid RAID, and also the benefit of RAID system. The implementation of RAID in modern operating systems, Windows 7 and Ubuntu 10.04, will give reader a sense of RAID systems at work.